2020
DOI: 10.3390/su12166634
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Variation and Climate Influence Factors of Vegetation Ecological Quality in the Sanjiangyuan National Park

Abstract: The Sanjiangyuan National Park is the first Chinese national park system, and the ecological environment is inherently fragile and sensitive. Therefore, for environmental protection, it is imperative to understand the spatiotemporal variation characteristics of the ecological quality of vegetation and its climate influence factors. We used the MODIS normalized difference vegetation index (NDVI) dataset, meteorological dataset, and Carnegie–Ames–Stanford Approach (CASA) model to investigate the spatiotemporal p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 40 publications
1
5
0
Order By: Relevance
“…The experimental results showed that the accuracy of direct vegetation index data fusion was higher, and in-depth studies such as surface vegetation cover can be conducted on this basis. The existing studies mostly applied the fusion model to Landsat and MODIS data [34], and the study of grassland cover change and toxic weed invasion in the TRHR also focused on medium-and low-resolution remote sensing data [35]. In contrast, Sentinel-2 had a higher spatial resolution compared to Landsat data, and the accuracy of monitoring the surface vegetation cover and change was also higher.…”
Section: Discussionmentioning
confidence: 99%
“…The experimental results showed that the accuracy of direct vegetation index data fusion was higher, and in-depth studies such as surface vegetation cover can be conducted on this basis. The existing studies mostly applied the fusion model to Landsat and MODIS data [34], and the study of grassland cover change and toxic weed invasion in the TRHR also focused on medium-and low-resolution remote sensing data [35]. In contrast, Sentinel-2 had a higher spatial resolution compared to Landsat data, and the accuracy of monitoring the surface vegetation cover and change was also higher.…”
Section: Discussionmentioning
confidence: 99%
“…Referring to the p-value selection of existing publications [34][35][36], vegetation changes were classified into six classes in this paper: Slope < 0 & p < 0.01 (extremely significant degradation), Slope < 0 & 0.01 < p < 0.05 (significant degradation), Slope < 0 & p > 0.05 (no evident degradation), Slope > 0 & p > 0.05 (no evident improvement), Slope > 0 & 0.01 < p < 0.05 (significant improvement), Slope > 0 & p < 0.01 (extremely significant improvement). To further quantify the spatio-temporal characteristics of vegetation growth trends within the mining area, the trend analysis was utilized to perform linear fitting and sig nificance tests for each pixel, revealing the temporal variations of NDVI.…”
Section: Evaluation Of Trends In Vegetation Growthmentioning
confidence: 99%
“…Simultaneously, human disturbances in the area have gradually decreased, especially in the core zone where human interference is strictly limited to scientific research purposes. In areas with minimal human interference, such as the core area, vegetation structure characteristics are primarily influenced by climate factors [41]. On one hand, climate change hinders or amplifies the natural succession process of different plant species, resulting in the extinction of certain plants in specific locations or the rapid expansion of climateadaptive plant species.…”
Section: Impacts Of Conservation Management On Vegetation Changes In ...mentioning
confidence: 99%